K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 9 2022

$y = \dfrac{2x + 5}{x - 2} = \dfrac{2(x - 2) + 9}{x - 2}= 2 + \dfrac{9}{x - 2}$

Để y ∈ Z thì $(x - 2) ∈ Ư(9) = {1 ; -1 ; 3 ; -3 ; 9 ; -9}$

x - 2xy
135
-11-7
355
-3-1-1
9113
-9-71

 

30 tháng 6 2015

Bài 1:

xy = x : y
<=> xy2 = x 
<=> y2 = 1 
<=> y = 1 hoặc y = -1 
-nếu y = 1 có 
x + 1 = x 
<=> 1 = 0 (loại) 
-nếu y = -1 có 
x - 1 = -x 
<=> x = \(\frac{1}{2}\)
thay vào thấy thỏa mãn 
Vậy x = 1\(\frac{1}{2}\) ; y = -1

30 tháng 6 2015

x+y=xy

=>x=y(x-1)

=>x:y=x-1

=>x-1=x+y

=>y= -1

Ta có -x=x-1

   <=>-2x=-1

   <=>x=0,5

26 tháng 6 2016

a) x=20

26 tháng 6 2016

b)\(x\in\left\{0;1;4;9;-2;-3;-6;-11\right\}\)

10 tháng 9 2016

\(a,2^{x+1}=3^y=12^x\Rightarrow2^{x+1}.3^y=2^{2x}.3y\)

\(\Rightarrow\frac{2^x}{2^{x+1}}=\frac{3^y}{3^x}\Rightarrow2^{2-x-x-1}=3^{y-x}\)

21 tháng 7 2017

lập bảng